The effect of purine content on sensory quality of pork. (February 2021) - Huang, Cong; Zheng, Min; Huang, Yizhong; Liu, Xianxian; Zhong, Liepeng; Ji, Jiuxiu; Zhou, Lisheng; Zeng, Qingjie; Ma, Junwu; Huang, Lusheng
Abstract: Although high level of purine in foods is considered a risk factor for hyperuricemia and gout, purine-rich foods continue to be popular for their delicious taste. The main objective of this study was to investigate the effects of purine bases on the sensory quality of pork. A total of 406 longissimus thoracis et lumborum samples were collected from a heterogeneous F6 pig population to determine purine composition and its correlation to sensory quality of pork. The contents of total purine and two major uricogenic bases (adenine and hypoxanthine) were negatively correlated with tenderness, juiciness, oiliness and overall liking ( r < −0.2, P < 0.05), but they were not significantly correlated with umami. In contrast, guanine content, which accounts for only about 10% of the total purine content, was positively correlated with umami ( r = 0.15, P < 0.05), and had no significant relationships with other sensory indicators. These results imply that purine bases with different uricogenic effects also influence different sensory quality indices of pork. Highlights: Lower contents of hypoxanthine and adenine in pork are associated with increased tenderness and juiciness. The guanine content enhances the umami taste of meat. Manipulation of different purine bases may improve both the nutritional value and sensory quality of meat.